Twinkle Kid's Studio / Kamisah Abdul Hakim ... [et al.] - Abdul Hakim, Kamisah; Ruslin, Rusila; Tuah, Malai Rosmah; Md Husain, Rushaida (Faculty of Art and Design, 2004)
We have decide to start our business with kid's studio and Twinkle Kid's Studio is a special name for our company. We choose this type of business because based on studies and observation in and around Shah Alam, there are no kid's photography service currently in order. Furthermore, all needs and demands are choose a good service and we have a skill knowledge and experience with the photography. Our company also offer to service in convocation of necessary, family day and more function. Our business location is ideally located at Lot 4,Jalan Bawal 3/B, Seksyen 18,40450 Shah Alam, Selangor Darul Ehsan and our office also situated at the same address. We choose Shah Alam area because we know that have there a lot of Malay people and by that point can easily reach our target market. From our viewpoint we have make forecasting that this business have a very good potential either in the current market or in the future. In conclusion, this business is really reasonable way gain high profit and to make any charge in future in order to develop and also to get global market.